The Mwera lamellophone Luliimba - Reuster-Jahn, Uta (International Library of African Music, 2007)
The lamellophone of the Makonde/Mwera type from south-eastern Tanzania and north-eastern Mozambique is a particular member of the family of lamellophones in Africa. It has been described by Margot Dias (1982, 1986, 1988) and Gerhard Kubik (1996, 1998), but until recently had not been studied in a performance context. This type of lamellophone has drawn scholarly interest because of its uniqueness. Kubik assumes that it could be the remnant of a small cradle area of lamellophones with metal keys in the lower Rovuma valley, apart from the large metal-keyed lamellophones found in Zimbabwe and the lower Zambezi valley (Kubik 1998:24 f). Furthermore, Kubik et al. point to a similarity of shape between Indonesian metallophones of the saron type and the Makonde/Mwera type of lamellophone, in terms of the curved box resonator and the roof-like top of the instruments.
Keywords: African Music